Factors Analysis of Influencing Tax Management with Indicators Effective Tax Rates for Food Companies Beverage Listed on the Indonesian Stock Exchange - Ermadiani; Rina Tjandrakirana DP; Burhanuddin (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research aims to investigate the influence of profitability, leverage, company size, and sales growth on tax management using the Effective Tax Rate (ETR) indicator in Food and Beverages companies listed on the Indonesia Stock Exchange during the 2018-2022 period. This research uses an associative approach in data analysis and multiple regression test methods with secondary data originating from company annual reports. The research results show that profitability as measured by Return on Assets (ROA) has a negative influence on tax management as measured by the Cash Effective Tax Rate (CETR). Leverage also has a negative influence on tax management, while company size has a positive influence on tax management. In addition, sales growth has a negative influence on tax management. These findings highlight the importance of these factors in determining the tax management policies of Food and Beverages companies in Indonesia. This research implies that company management can consider profitability, leverage, company size, and sales growth in planning their tax strategies.